FAKTOR-FAKTOR YANG MEMPENGARUHI KEMANDIRIAN KEUANGAN DAERAH PADA KABUPATEN/KOTA DI WILAYAH PROVINSI KALIMANTAN SELATAN TAHUN 2007-2016 - MAULIDA UTAMI (PPJP Universitas Lambung Mangkurat, 2018)
This research has a purpose to see how the impact of Local Own Revenue, Gross Domestic Regional Product and General Allocation Funds on theFinancial Self Sufficiency in Regency/Cities in South Kalimantan Province. The population of this study are 13 Regency/Cities in South Kalimantan during 2007-2016. This research is descriptive and quantitative research and using secondary data obtained by DJPK and BPS. Analysis technique with multiple linear regression analysis method.The results of this sutdy indicate that Local Own Revenue impact positive effect, Gross Domestic Regional Product did not effect and General Allocation Funds impact negative effect on the level of Financial Self Sufficiency.Regions with mining mainstay sectors have low Financial Self Sufficiency while areas with non-mining mainstay sector have a high Financial Self SufficiencyKeywords : Financial Self Sufficiency, Local Own Revenue, Gross Domestic Regional Product, General Allocation Funds